2016
DOI: 10.1002/dta.1930
|View full text |Cite
|
Sign up to set email alerts
|

In vitro metabolism study of a black market product containing SARM LGD‐4033

Abstract: Anabolic agents are often used by athletes to enhance their performance. However, use of steroids leads to considerable side effects. Non-steroidal selective androgen receptor modulators (SARMs) are a novel class of substances that have not been approved so far but seem to have a more favourable anabolic/androgenic ratio than steroids and produce fewer side effects. Therefore the use of SARMs has been prohibited since 2008 by the World Anti-Doping Agency (WADA). Several of these SARMs have been detected on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 27 publications
(58 reference statements)
2
52
0
Order By: Relevance
“…33 A study of healthy young men 35 proved that LGD-4033 is safe, well-tolerated, has favorable pharmacokinetic profile with a prolonged elimination half-life (24-36 hours), and shows lean body mass increase. 42 The in vitro (in human) liver microsomes metabolites 34,40 as well as by electrochemical conversion/microbial degradation metabolites of While its use is unofficially approved and it is not yet manufactured by a pharmaceutical company, many websites make LGD-4033 widely available 36-38 and studies have reported its detection in black market products.…”
mentioning
confidence: 99%
“…33 A study of healthy young men 35 proved that LGD-4033 is safe, well-tolerated, has favorable pharmacokinetic profile with a prolonged elimination half-life (24-36 hours), and shows lean body mass increase. 42 The in vitro (in human) liver microsomes metabolites 34,40 as well as by electrochemical conversion/microbial degradation metabolites of While its use is unofficially approved and it is not yet manufactured by a pharmaceutical company, many websites make LGD-4033 widely available 36-38 and studies have reported its detection in black market products.…”
mentioning
confidence: 99%
“…9,28 The product ions observed in the spectra of M5 (Table 1) This metabolite has previously been reported following an in vitro study of LGD-4033 with human microsomes, and was later identified in human urine.…”
Section: Identification Of In Vitro Metabolitesmentioning
confidence: 86%
“…Due to the ease of availability over the internet, the misuse of LGD-4033 has already been reported in the human sports arena, 8 highlighting the need for routine methods that allow the best possible detection of these novel substances in doping control laboratories. 9,10 Numerous other SARMs have also been studied in the human. As a result, studies have been carried out utilising human liver microsomes to investigate the human metabolism of LGD-4033 products in vitro.…”
Section: -Yl)-2-(trifluoromethyl)-benzonitrile) Is a Member Of A CLmentioning
confidence: 99%
“…As the best studied SARM, GTx‐024 has been evaluated in phase III clinical trials for the treatment of muscle wasting in patients with non‐small‐cell lung cancer and is now under phase II trials for stress urinary incontinence and AR + TNBC etc (NCT02658448, NCT02971761). LGD‐4033 is an oral SARM under development by Ligand Pharmaceuticals Inc (LGND) . In a phase I clinical trial, it appeared to be safe and increased the lean body mass of healthy young male in a short period without changing the value of PSA .…”
Section: Ar and Anabolic Deficienciesmentioning
confidence: 99%